Potential for Pharmacy–Public Health Collaborations Using Pharmacy-Based Point-of-Care Testing Services for Infectious Diseases. Issue 6 (November 2017) - Gubbins, Paul O.; Klepser, Michael E.; Adams, Alex J.; Jacobs, David M.; Percival, Kelly M.; Tallman, Gregory B.
Abstract : Context: Health care professionals must continually identify collaborative ways to combat antibiotic resistance while improving community health and health care delivery. Clinical Laboratory Improvement Amendments of 1988 (CLIA)-waived point-of-care (POC) testing (POCT) services for infectious disease conducted in community pharmacies provide a means for pharmacists to collaborate with prescribers and/or public health officials combating antibiotic resistance while improving community health and health care delivery. Objective: To provide a comprehensive literature review that explores the potential for pharmacists to collaborate with public health professionals and prescribers using pharmacy-based CLIA-waived POCT services for infectious diseases. Design: Comprehensive literature review. Setting: PubMed and Google Scholar were searched for manuscripts and meeting abstracts for the following key words: infectious disease, community pharmacy, rapid diagnostic tests, rapid assay, and POC tests. Intervention: All relevant manuscripts and meeting abstracts utilizing POCT in community pharmacies for infectious disease were reviewed. Outcome Measure: Information regarding the most contemporary evidence regarding CLIA-waived POC infectious diseases tests for infectious diseases and their use in community pharmacies was synthesized to highlight and identify opportunities to develop future collaborations using community pharmacy-based models for such services. Results: Evidence demonstrates that pharmacists in collaboration with other health care professionals can leverage their knowledge and accessibility to provide CLIA-waived POCT services for infectious diseases. Testing for influenza may augment health departments' surveillance efforts, help promote rationale antiviral use, and avoid unnecessary antimicrobial therapy. Services for human immunodeficiency virus infection raise infection status awareness, increase access to health care, and facilitate linkage to appropriate care. Testing for group A streptococcal pharyngitis may curb inappropriate outpatient antibiotic prescribing. However, variance in pharmacy practice statues and the application of CLIA across states stifle collaboration. Conclusion: CLIA-waived POCT services for infectious diseases are a means for pharmacists, public health professionals, and prescribers to collaboratively combat antibiotic resistance and improve community health. Abstract : Supplemental Digital Content is Available in the Text.